(untitled) (Advances in Knowledge Representation, 2021)
This essay is dedicated to the study of ontology, an interdisciplinary research field that examines entities and relationships as a mean for better-performing knowledge domains modeling. There is a growing interest in the application of ontologies for problem-solving in several areas, such as Computer Science, Information Science, Philosophy, Artificial Intelligence, Linguistics, Knowledge Management; as well as within knowledge domains, such as Health, Biomedicine, Law, Geography, to name a few. Our approach here is called "Applied Ontology", a field that gathers new technologies, in particular those developed for the Semantic Web, together with solid metaphysical philosophical foundations. We present basic information about ontology and its application in information systems.